Investigation on different compositions of flyash concrete on gamma and neutron radiation - Ramli R.; Mohamad Idris F.; Yapandi M.F.K.M.; Saad J.; Akmal Biyamin S. (Institute of Physics Publishing, 2023)
Coal ash; Coal combustion; Concrete mixtures; Fly ash; Gamma rays; Mixtures; Neutrons; Portland cement; Waste incineration; Coal combustion products; Concrete productions; Fly ash concretes; Gamma irradiation; Neutron radiations; Partial replacement; Radiation materials; Small angle scattering; Neutron irradiation